2021
DOI: 10.3389/fonc.2021.668261
|View full text |Cite
|
Sign up to set email alerts
|

Being a Myeloproliferative Patient in COVID-19 Era: The Mytico Study

Abstract: IntroductionThe Coronavirus disease 2019 (COVID-19) pandemic and the resulting social distancing, determined a reduction in access to care and limitations of individual freedom, with a consequent strong impact on quality of life (QoL), anxiety levels and medical management of onco-hematological people. In particular, in the case of patients with chronic myeloproliferative neoplasm (MPN), concern about SARS-CoV-2 infection added to the burden of symptoms (BS) which already weights on the QoL of these patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Our data confirm the assumption that physical activity acts as a protective factor, preventing chronically ill patients from developing threatening fears, such as limited medical care during COVID-19 pandemic or from postponing medical appointments. Previous studies showed a correlation between higher anxiety and depression levels and a lack of physical activity ( 35 ), suggesting that increased physical activity might lower the psychological burden in ACHD patients, resulting in less canceled appointments and a higher satisfaction with the level of medical treatment. Moreover, it was described that doing sports according to patients individual physical capacity has a direct positive effect on their health by reducing inflammatory markers and BMI ( 42 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our data confirm the assumption that physical activity acts as a protective factor, preventing chronically ill patients from developing threatening fears, such as limited medical care during COVID-19 pandemic or from postponing medical appointments. Previous studies showed a correlation between higher anxiety and depression levels and a lack of physical activity ( 35 ), suggesting that increased physical activity might lower the psychological burden in ACHD patients, resulting in less canceled appointments and a higher satisfaction with the level of medical treatment. Moreover, it was described that doing sports according to patients individual physical capacity has a direct positive effect on their health by reducing inflammatory markers and BMI ( 42 ).…”
Section: Discussionmentioning
confidence: 98%
“…In our study, postponed medical appointments were independently predicted by female sex. During the COVID-19 pandemic observed sex disparities derived from the general population point to a higher vulnerability of women to develop depressive and anxiety symptoms ( 35 ).…”
Section: Discussionmentioning
confidence: 99%